Color atlas of veterinary histology - Bacha, William J.; Bacha, Linda M. (John Wiley & Sons, 2012)
Designed to provide students with a foundation in understanding and interpreting histologic and cytologic preparations, Color Atlas of Veterinary Histology is a practical benchside reference focusing on the normal histology of eight common domestic species